2021
DOI: 10.1108/ebr-09-2020-0231
|View full text |Cite
|
Sign up to set email alerts
|

Facing and responding to the COVID-19 threat – an empirical examination of MSMEs

Abstract: Purpose The purpose of this study is to examine the effects and ways to confront the devastating effects of the COVID-19 crisis and develop a theoretical framework to facilitate understanding of these aspects from the perspective of micro, small and medium enterprises (MSMEs). In doing so, the fundamental insights of entrepreneurial self-efficacy, bricolage and improvisation are considered. Design/methodology/approach The study draws on data from 56 business owners-managers operating in eight different natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 52 publications
(65 reference statements)
2
32
0
Order By: Relevance
“…The advantage of CM‐as‐practice is that, rather than departing from an optimum according to which firms should be fully prepared to deal with the crisis through business continuity plans, analytical methods, and specific crisis teams, it zooms in on the actors and arenas where crisis management is conducted. In line with contemporary research on crisis management (see especially, Alonso et al, 2021 ; Kim & Lim, 2020 ; Kuckertz et al, 2020 ; Tyler et al, 2020 ), our results show clearly that we should not expect these SMEs to have any of the features of the planning paradigm. Instead, they rely on established arenas and, if anything, they seem to become less reliant on input from others, which previous studies have shown to be a success factor in crisis management (Elliott et al, 2010 ; Sauser et al, 2018 ; Torres et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The advantage of CM‐as‐practice is that, rather than departing from an optimum according to which firms should be fully prepared to deal with the crisis through business continuity plans, analytical methods, and specific crisis teams, it zooms in on the actors and arenas where crisis management is conducted. In line with contemporary research on crisis management (see especially, Alonso et al, 2021 ; Kim & Lim, 2020 ; Kuckertz et al, 2020 ; Tyler et al, 2020 ), our results show clearly that we should not expect these SMEs to have any of the features of the planning paradigm. Instead, they rely on established arenas and, if anything, they seem to become less reliant on input from others, which previous studies have shown to be a success factor in crisis management (Elliott et al, 2010 ; Sauser et al, 2018 ; Torres et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, Drabek ( 1985 ) and Stallings and Quarantelli ( 1985 ) pointed out that effective crisis management also includes ad hoc abilities, such as improvised decision‐making. These types of improvisational abilities is oftentimes referred to as bricolage, which includes the notion of seeking to respond and adapt to an unprecedented event (Alonso et al, 2021 ), such as the COVID‐19 pandemic. Thus, there are two fundamentally different approaches that have been described as successful, although Williams et al ( 2017 ), based on their review of previous studies, stated that successful crisis management requires a balance between structure and flexibility.…”
Section: Crisis Management As Practicementioning
confidence: 99%
“…Tourists perceptions of risk associated with the spread of the pandemic have resulted in changing patterns of mobilities and radical shifts in patterns of consumer demand to which businesses have to adapt (Korinth, 2020;Kowalska and Niezgoda, 2020;Neuburger and Egger, 2020;Sánchez-Cañizares et al, 2020;Godovykh et al, 2021;Rogerson and Rogerson, 2021a). Seemingly, the ways that tourism businesses are confronting and responding to the debilitating effects of the COVID-19 pandemic vary geographically across different regions of the world as is shown by the eight country study undertaken by Alonso et al (2021aAlonso et al ( , 2021b.…”
Section: Introductionmentioning
confidence: 99%
“…Africa is one continent that was not included in the rich multi-country research reported by Alonso et al (2021aAlonso et al ( , 2021b. The aim in this paper is to address this knowledge gap by examining tourism business responses in South Africa, seemingly the country worst hit on the African continent by the COVID-19 crisis Rogerson, 2020a, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…The USA, in dealing with Covid-19 accelerated the preparation process at the health system level by regulating the public response, but the response was not optimal (Loungani et al, 2020); besides the impact of transmission caused a very rapid increase in cases and had a significant impact on the readiness of health workers (Chen et al, 2020). The government needs to respond to Covid-19 by identifying gaps and government readiness in responding to the pandemic by looking at what happened in Italy (Duarte Alonso et al, 2021). While the government's social distancing policy has not been able to suppress the spread of the epidemic, even the social distancing policy is considered an uncertain policy (Galvin, Fernandez-Luque, and Li, 2020).…”
Section: Government Response To Covid-19mentioning
confidence: 99%